Smartphone Addiction among UTHM Students - Nasuredin, Juzaimi; Rashid, Umi Kartini; Ismail, Fadillah (Research in Management of Technology and Business, 2020)
This research aims to study the relationship between smartphone addiction and the characteristics of smartphone use among UTHM students. Smartphone users’ characteristics such as tolerance, withdrawal, positive expectancy, and interference with daily routine affected smartphone addiction. There is a lack of local studies regarding smartphone addiction; therefore, this study carried out to demonstrates it. This study selected 375 respondents from students UTHM, and an online survey questionnaire was established to collect data. The questionnaires successfully collected from 283 respondents in UTHMs included the campus of Parit Raja and Pagoh. Data obtained was analysed using SPSS version 21. Statistical results confirmed the significant relationships between tolerance, withdrawal, positive expectancy, and interference, and smartphone addiction.